Decentralised Traffic Management for Constrained Urban Airspace: Dynamically Generating and Acting Upon Aggregate Flow Data - Morfin Veytia, Andres; Ellerbroek, Joost; Hoekstra, Jacco (Journal of Open Aviation Science, 2024)
There are several efforts to explore employing drones to replace ground transportation in cities. However, this would mean that the expected traffic densities would be significantly higher than existing air traffic management. A decentralised system for traffic management may be necessary in this future because (1) not all airspace actors will want to freely share data, (2) the uncertainty of missions due to wind or other factors could make a previous plan inoperable, and (3) the ad hoc nature of urban missions makes them difficult to plan in advance. This work focuses on the challenges of drone operations within constrained urban airspace. We define constrained airspace as a virtual network overlaid on the physical environment, where tall buildings and urban infrastructure dictate the allowed routes. Drones are restricted to flying within this virtual network, either above the existing street network or along other predetermined segments. A dynamic and decentralised traffic management method is presented. The method uses current aggregate flow data to identify and alter the cost of travelling through high-density clusters. The goal is to reduce local traffic density and complexity by encouraging alternate routes. Three different clustering strategies are presented that look at the current position of aircraft and recent safety events. The dynamic traffic management method is first illustrated with two simple example scenarios. Then an experiment is conducted with different traffic demand levels within the city of Rotterdam. It was observed that when using traffic complexity indicators, the method is able to reduce safety events by 30 percent while only increasing the distance travelled by 6 percent.